2010
DOI: 10.1002/gcc.20825
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 and VGLL3, encoding two cofactors of TEAD transcription factors, are amplified and overexpressed in a subset of soft tissue sarcomas

Abstract: In a series of 404 adult soft tissue sarcomas, analyzed by array-CGH, we have observed in approximately 10% of them a genomic amplification of either chromosome bands 11q22 or 3p12. These two amplicons likely target the YAP1 and VGLL3 genes, respectively. Both genes encode proteins that are cofactors of the TEAD family of transcription factors. Very good correlations between amplification and expression levels were observed. Welch test analyses of transcriptome data demonstrate that tumors with amplicons share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 28 publications
2
104
1
Order By: Relevance
“…Previous studies showed that VGLL1 promotes cell proliferation and exhibits high expression in basal-like breast cancer [29,30]. Similarly, VGLL3 is amplified in soft tissue sarcoma and inhibition of VGLL3 results in decreased cell proliferation and migration [31]. Different from other members in VGLL family, VGLL4 contains an extra TDU domain and is considered to be functionally different.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that VGLL1 promotes cell proliferation and exhibits high expression in basal-like breast cancer [29,30]. Similarly, VGLL3 is amplified in soft tissue sarcoma and inhibition of VGLL3 results in decreased cell proliferation and migration [31]. Different from other members in VGLL family, VGLL4 contains an extra TDU domain and is considered to be functionally different.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that mutations in the Hippo pathway are more common than previously thought (8,12). Furthermore, Hippo pathway genomic deletions/amplifications and gene expression changes have been detected in a variety of malignancies including STS (13). However, little is known about the status of the Hippo pathway in adult STS, although MST1/2 appears to be epigenetically silenced through promoter hypermethylation in a limited number of sarcoma patient samples (14).…”
mentioning
confidence: 99%
“…Moreover, Antonescu et al (63) confirmed the presence of high level VGLL3 amplification by FISH in MIFS, as well as in HFLT and cases with hybrid morphology. VGLL3 has been shown to be amplified and overexpressed in undifferentiated pleomorphic sarcoma and dedifferentiated liposarcoma (66). These findings suggest that VGLL3 is the main target of 3p12 amplification and this genetic event may be crucial in the development and progression of certain subsets of soft tissue sarcomas.…”
Section: Intermediate Soft Tissue Tumorsmentioning
confidence: 94%